Beyond the “one gene-one disease” paradigm: complex genetics and pleiotropy in inheritable cardiac disorders - Cerrone, Marina (Circulation, 2019)
Inheritable cardiac disorders often associate with increased risk of sudden death in the young, as well as with structural damage to the myocardium. Early linkage analysis studies in Mendelian forms of these diseases, such as hypertrophic cardiomyopathy and long QT syndrome, uncovered large-effect genetic variants that contribute to the phenotype. In more recent years, through genotype-phenotype studies and methodological advances in genetics, it has become evident that most inheritable cardiac disorders are not monogenic but rather, have a complex genetic basis wherein multiple genetic variants contribute (oligogenic or polygenic inheritance). Conversely, studies on genes underlying these disorders uncovered pleiotropic effects, with a single gene affecting multiple and apparently unrelated phenotypes. In this review, we explore these two phenomena: on one hand, the evidence that variants in multiple genes converge to generate one clinical phenotype and on the other, the evidence that variants in one gene can lead to apparently unrelated phenotypes. While multiple conditions are addressed in order to illustrate these concepts, the experience obtained in the study of Long QT Syndrome, Brugada syndrome and of arrhythmogenic right ventricular cardiomyopathy, as well as in the study of functions related to SCN5A (the gene coding for the alpha-subunit of the most abundant sodium channel in the heart) and PKP2 (the gene coding for the desomosomal protein plakophilin-2) is discussed in more detail.